Characterization of monoclonal antibody fragments produced by plant cells - Sharp, J.M.; Doran, P.M.
Production of a murine IgG1 was investigated using hairy roots, shooty teratomas, and suspended cells of transgenic tobacco. In all cases, in addition to complete assembled antibody, two to four major antibody fragments accumulated in the biomass. A range of protease inhibitors, protein-stabilizing agents, inhibitors of N-glycosylation and protein secretion, glycan-reactive agents, and affinity probes was used to characterize these fragments and investigate their sites and mechanisms of formation. The fragments were not experimental artifacts caused by antibody degradation during tissue homogenization and sample preparation, nor did they represent glycosylation variants. All of the molecules were actively secreted into the culture media and some showed evidence of Golgi-associated glycan processing, indicating they were not assembly intermediates. Antibody fragments of 50 and 80 kDa were identified mainly as the products of extracellular degradation in the root and shoot apoplast; the 80-kDa fragment was also present in cell suspension medium, and in suspended cell biomass toward the end of the growth phase. Larger 120- and 135-kDa fragments were most likely produced by proteolytic degradation along the secretory pathway outside of the endoplasmic reticulum (ER)and Golgi apparatus; the carbohydrate residues of the 135-kDa antibody suggest formation between these organelles. Inhibition of protein secretion and retention of antibody in the ER and/or Golgi reduced fragmentation and increased antibody accumulation levels, probably by reducing exposure to the principal sites of protease activity. This work highlights the importance of foreign protein degradation in plant tissues as a mechanism for posttranslational product loss. Identifying the nature of these degradative processes is a first step toward alleviating their effects, improving protein yields, and enhancing the feasibility of plants as a commercial means for large-scale protein production.
Keywords: FOREIGN PROTEINS; MONOCLONAL ANTIBODY; PROTEIN STABILITY; PLANT CELL SUSPENSIONS; HAIRY ROOTS; ANTIBODY FRAGMENTS